Educational activities in the conditions of educational inclusion: phenomenon, specifics, advantages - E.M. Safronova; T.A. Bondarenko (Психолого-педагогические исследования)
Context and relevance. Since inclusive education is a legal requirement in the Russian Federation, the issues of organizing education in non-standard conditions for teachers and parents need special research and reflection. At the same time, pedagogical science, in particular, the theory of education, the concept of inclusive education, faces a number of questions: Who is the subject of education in the context of inclusion? Is there an additional educational resource in inclusive education? Objective. Clarification of the phenomenon of educational activity, its specifics and advantages in the context of inclusion in modern Russian education. Hypothesis. Educational activities in the context of inclusive education retain the key characteristics of upbringing as a priority function of education, while acquiring the specifics and advantages associated with the implementation of the predicates of inclusive practice (participation, acceptance, psychological and pedagogical support, accessibility). Methods and materials. The research is mainly theoretical in nature, in connection with which the authors used methods of analyzing scientific literature, comparing the points of view of various researchers in the field of general and special pedagogy on the phenomenon of educational activity, a method of generalizing scientific positions, as well as methods of analyzing empirical experience and interviewing future teachers. Results. The phenomenon of educational activity in conditions of inclusion, its specifics and advantages are described; the grounds for using an individually differentiated approach in these conditions are substantiated. Conclusions. The characteristics of education identified and described by the authors in accordance with the predicates of inclusive practice help to identify the presence of "inclusive education" in school, and can also be used as guidelines for analysis/self-analysis and assessment of the state of educational activities, taking into account the special educational needs of pupils. Promising educational projects such as the description of inclusive educational practices based on an evidence-based approach can be implemented more successfully if the advantages and grounds of an individually differentiated approach specified by the authors are taken into account.